DAMPAK EKONOMI PENGURANGAN SUBSIDI BBM - Budiono Sri Handoko (Universitas Muhammadiyah Yogyakarta, 2006)
This paper attempts to analyze economic impact of fuel subsidy cuts. The economic impacts include economic growth indicator, inflation, employment, and poverty. By using Applied General Equilibrium Model, we find that an increase in fuel prices cause the economic growth and employment declines, and the other side there is inflation. The simulation result which using SUSENAS data shows that an increase in fuel prices can increase poverty, assumed that compensation program wasn‘t effective.